Edukasi CBPR (Cinta Bangga Paham Rupiah) dan Anti Bullying Melalui Kuliah Kerja Nyata Mahasiswa Universitas Sembilanbelas November Kolaka - Mardiana Mardiana; Satriana Satriana; Yulianda Yulianda; Muhamad Rifal Febrian; Sri Agustini; Hafsiana Hafsiana; Ali Slamat; Sarmila Sarmila; Syamsidar Fathanah Hardin; Yendri Sri Maryani; Lusyana Limbong; Sri Wahyuni; Rahel Oktavia Palimbong; Siarni Siarni (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
The community service program carried out through the Community Service Program (KKN) of Universitas Sembilanbelas November Kolaka aims to address the low level of financial literacy and the increasing incidence of bullying among students in Tontonunu Village. Limited access to information, insufficient understanding of the functions and value of the Rupiah, and the lack of awareness of the socio-psychological impacts of bullying make CBPR (Love, Proud, Understand Rupiah) and Anti Bullying education highly relevant and necessary. The community service activities were implemented through participatory socialization, group discussions, and interactive question and answer sessions. The evaluation of program effectiveness employed pre-test and post-test instruments, observation sheets, interviews, and field documentation. The results indicated an improvement in students’ knowledge regarding the authenticity features of the Rupiah, responsible financial behavior, and understanding of the forms and impacts of bullying. Participants also demonstrated positive changes in communication patterns and increased empathy toward others. These findings emphasize that participatory-based education can provide tangible impacts in strengthening students’ financial literacy and social awareness. Overall, the program significantly contributes to fostering positive character development and promoting a healthier and safer educational environment free from bullying.